Gender and Working Life - Bergholm, Tapio; Gonäs, Lena; Juul, Ida (Nordic Journal of Working Life Studies, 2011)
Analysis of occupational segregation by sex and gendered practices in the workplace are complex, multidimensional and contested fields of research and academic discourse. Since the 1960s, we have seen a rapid growth in both quantity and quality of academic work in this field. Earlier simplistic main (male) stream as well as straightforward feminist explanations has been roundly criticised and deconstructed. It is now clear that the study of gender relations in working life is far more complicated than it was believed decades ago. The central question in gender research is how gendered structures – in which men in general have more power, more prestigious positions and higher pay – are reproduced in a world in which demography, economy, production, education and therefore society and family have changed over time. Nordic countries represents an interesting geographical arena to examine gender relations in working life, because many factors, which have been seen in other countries as causes for female subordination, appear in other forms. At present, the labour force participation rate of women in Nordic countries is nearly equal to that of men, but there are still substantial differences. Women are better educated than men, and also, to a large extent unionised. Although these factors make Nordic women stand out globally, gender equality at work or at home has not yet been achieved. The male breadwinner is still a societal norm and a construct, which conditions the behaviour of organisations and individuals in many circumstances in working life. This influence can be obvious or obscure. From the 1990s, research has turned to focus also on the fate of the male workforce during deindustrialisation and global restructuring. Participation rate of men in gainful employment have diminished in all industrialised countries (Crouch; 1999, Walby; 1997). Nordic countries are not an exception to this trend. Men’s difficulties to adapt to a new service- and care society offers new perspectives on the rigid gendered segregation of industries and occupations in Nordic countries (Bergholm; 2011.) (...)